COMPARATIVO DE PRODUCCION DE PRUEBA ANTICIPADA ENTRE EL CODIGO DE PROCESO CIVIL DEL 2015 BRASILEÑO CON EL CODIGO DE PROCESO CIVIL DEL 2007 HONDUREÑO. - Reyes, Emerson Noe Guevara (2020)
This study analyses is to demonstrate that the current autonomous action about of the Anticipated production of evidence in Civil Procedure Law of 2015, could be implemented under the legal reality of the Honduran law submitted in the Code of Civil Proced